Affirmative action: perception of the “Casa Grande” and the “Senzala” - Silvério, Valter Roberto (Universidade Estadual Paulista / UNESP, 2007)
The late 70’s point towards the debut of several social movements in the scenario, both new and traditional, among which is the black movement that reintroduces the racial theme as a relevant social issue. Firstly, the black movement denounced the existence and persistence of discriminatory racist practices and subsequently began demanding concrete measures from gubernatorial instances in the sense of constraining these. These denunciations and claims are part of a broader context of struggles, which called for changes in the approach of social issues by Brazilian state. This dynamic process has allowed a broader view of the dispute between a political project which continues to follow the authoritarian tradition and another which points towards the necessity of a democratic updating in the process of choosing routes for the country.